Respuesta :
The x-intercept is 3 and 7. The answer is incorrect, the user shouldn't have negated the given values of x.
Given the expression f(x) = (x − 3)(x - 7)
The x-intercept of the line occurs at the point where f(x) = 0
Substitute f(x) = 0 into the expression as shsown:
f(x) = (x − 3)(x - 7)
0 = (x − 3)(x - 7)
x - 3 = 0 and x - 7 = 0
x = 3 and 7
Hence the x-intercept is 3 and 7. The answer is incorrect, the user shouldn't have negated the given values of x.
Learn more here: https://brainly.com/question/1744326